EXPLORING ANTECEDENTS OF SUSTAINABLE PERFORMANCE IN FASHION INDUSTRY, USING A SYSTEMATIC LITERATURE REVIEW APPROACH - Bazkiaei, Raheleh Alipour; Zainol, Amer Shakir (JOURNAL OF TOURISM, HOSPITALITY AND ENVIRONMENT MANAGEMENT (JTHEM), 2025)
The fashion industry as one of the largest sectors globally, is among the most resource-consuming in the world regarding environmental impact. The fashion firms consist of the different phases of design and production, the activities which are not mostly eco-friendly. On another side, the growing demand for sustainability in this industry has provoked a move in the way firms approach their activities. In the recent past, different changes have been observed in design and production for an improved environmental and social performance to achieve sustainability goals. Hence, with the purpose of exploring and reviewing the available research on sustainable performance and green practices, this study used a systematic literature review protocol. Applying narrative synthesis method and using the Web of Sciences and Scopus databases, it analysed the latest literature from 2014 to 2024 to assess the significant role fashion designers play to drive sustainability trends within the fashion industry. By exploring key concepts such as green practices and the integration of technologies, this paper identified how these approaches contribute to social, economic, and environmental sustainability. The review combined existing studies, highlighting key trends, and factors that fashion designers employ in integrating sustainability into their work, offering insights for future research.